2021
DOI: 10.3389/fmars.2021.663856
|View full text |Cite
|
Sign up to set email alerts
|

Cayman Islands Sea Turtle Nesting Population Increases Over 22 Years of Monitoring

Abstract: Given differing trajectories of sea turtle populations worldwide, there is a need to assess and report long-term population trends and determine which conservation strategies are effective. In this study, we report on sea turtle nest monitoring in the Cayman Islands over a 22-year period. We found that green (Chelonia mydas) and loggerhead (Caretta caretta) nest numbers increased significantly across the three islands since monitoring began in 1998, but that hawksbill nest numbers remained low with a maximum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“… The key events of the Cayman Islands green turtle populations are detailed, including their decline, the captive breeding, the reintroduction program and the recent recovery. The dashed white line represents the wild population showing the initial decline until its virtual extinction 24 and later increase 25 . The green dot on the dashed line represents the discovery of the first nests laid by wild females.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… The key events of the Cayman Islands green turtle populations are detailed, including their decline, the captive breeding, the reintroduction program and the recent recovery. The dashed white line represents the wild population showing the initial decline until its virtual extinction 24 and later increase 25 . The green dot on the dashed line represents the discovery of the first nests laid by wild females.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we show that assisted colonisation can establish sea turtle nesting populations and we also provide insight on factors related to feasibility and long-term viability. For sea turtles, important considerations for captive breeding include animal husbandry and welfare concerns, the potential for disease transfer through the release of animals from an intensive-rearing facility into the wild, high costs, and apparently low rates of recruitment of captive-bred individuals into wild nesting populations 25 . In this study, we showed the results from more than 25,000 yearling and hatchling turtles released in the 1980s 27 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolific historical commercial exploitation devastated the abundance of nesting turtles in the British Virgin Islands (Richardson et al, 2006), Jamaica (Amorocho et al, 2016), and the Cayman Islands (Fleming, 2001). While population recoveries have occurred in recent years, the abundance of nesting turtles remains a small fraction of what existed historically (Blumenthal et al, 2021). That the unregulated, historical, large-scale commercial harvest was demonstrably unsustainable is clear.…”
Section: Cheloniansmentioning
confidence: 99%